Determining scalar illuminance from cubic illuminance data. Part 2: Tests in real lighting environments and an approach to improve its accuracy. (January 2023) - Xia, L; Gu, Y; Liu, X; Zhang, T; Xu, R
Scalar illuminance, which describes the constant illumination from all directions, is an important indicator of the abundance of light for a lit object and the adequacy of illumination perceived. This paper proposes a more reliable method to recover scalar illuminance based on tests in natural complex lighting environments. The performance of Cuttle's Approach 1, Mangkuto's Approach 2 and Approach 3, together with Xia et al. 's potential Approach 4, were tested under a total of 610 high dynamic range (HDR) panoramic maps of real scenes. The relationships between predicted scalar illuminance and normalised diffuseness levels were checked. The results indicate that the potential Approach 4 is more robust to the cubic meter's postures, and the predicted scalar illuminance has a regular relationship with normalised diffuseness levels. Approach 4 was corrected, together with Approach 1, formulating a new method named Approach 5S. Later, the proposed Approach 5S was evaluated under 205 indoor and 2233 outdoor panoramas from the Laval HDR databases, and it was shown to recover more reliable scalar illuminance with an average error within 5% in general. This study has provided a practical solution to more accurate vector illuminance-based metrics in real lighting environments. This algorithm can be further integrated into the development of cubic illumination meter instruments.